Atenção primária à saúde arquitetura e urbanismo, instrumentos de sua materialização físico-espacial - Carmen Fabiana Cardoso (2006)
The object of this study is the union of architectura, the primary atention health and popular participation, incluing the politic sistem of participative democracy, of Sistema Único de Saúde (SUS Unique Sistem of Health) and paradigms of Social Production of Health. The objective is investigate the directrizes for the elaboration of architecture projects of Unidade Básica de Saúde (UBS Basic Unity of Health integrated in Communitary Centers, so as directrives to urban intervention in the next having the communitary participation as reference. The study begins at referencial theoretical Marxist dialetic, propos the search of intervention and use the qualitative board. So, was utilized this procedure: bibliography and documentary search and study of case in municip of Belo Horizonte with insurrection or/and elaboration of maps, open interviews audio-records and integrality transcripted with twelve informants from various setors of the area, definition of the place aim of study, with visits and elaboration of programe of necessitys for the basic point of the selected area.The results of this studys shows, havin the search as base, the distance between the goal and the challenge in acordo f National Plane of Health 2004/2007. According to the norms wich regards the construction and reform of UBS cam be observed the advance of RDC no 50 when it doesnt defined a normal project and the obstacle when it was directonade to wery levels of atention, so very abrangent and few especific; so as the advance in Resolution no 604 of SES/MG when directionated to primary attention with lasy usefull. Was possible, beginings at metodology, define the local área of intervention the UBS Santa Rita de Cássia. In front of the found reality, the existence of the intersetorial programe BH citizenship, abandon, in this case, the idea of fisical integration of UBS with the comunitary centre, taking in consideration the existence of BH centre citizenship in final phase ofimplantation of the unity in the local area. Was definide the architectoniques programe to UBS Santa Rita de Cássiashowing the importance of this how easiler instrument to begins a process of collective construction thinking of the futures users of the new fisical space, with the objective of responsabilization and participation of big part, adding to space a feeling of belongs and appropriation of users of fisical space growing the citizenship exercicies. At last, in conclusion the architecture must to be more and more useful how a potential partnerof public health, in primary special atention, in direction of develop spaceswich potentialize the proposal actions, favour the production of care and contribute with UBS, for the consolidation of your orde how as the enter door for SUS.